FORMULASI SEDIAAN LOSION ANTIOKSIDAN EKSTRAK AIR DAUN TEH HIJAU (Camellia sinensis L.) - Fahrauk Faramayuda; Fikri Alatas; Yesi Desmiaty (Majalah Obat Tradisional, 2010)
The research about lotion dosage formulation that contain green tea leaf water extract with concentration 0.0002%, 0.002%, 0,02%, and 8.6% had been done. The basic of the EC50 value. Which calculated from linierity regression equation between tested solution concentration and scavenging percent. The lotion formulation began with lotion base orientation included organoleptic, homogeinity, pH, and viscosity. It showed that lotion base with glyceryl monostearate 5.5% have the best pH stability, viscosity, and consistency. Evaluation of lotion dosage include physical evaluation (organoleptic, homogeinity, viscosity and stability) and chemical evalution (pH and the stability of lotion antioxidant activity. Antioxidant activity stability evaluation of lotion with 1,1-diphenyl-2-picrylhidrazyl solution using spectrophotometri UV-Visible showed, that formula which contain 0.02% and 8.6% green tea leaf water extract gave the best radical scavenging activity and stable during storage.